THE WORKABILITY AND DURABILITY PROPERTIES OF DUCTILE SELF COMPACTING CONCRETE WITH CEMENT REPLACEMENT MATERIALS - CHANG, KOK YUNG (2014)
Ductile self compacting concrete (DSCC) is one of the advanced materials which combines self compacting abilities and ductility to address the current industry problems. Due to the increasing production of cement, it constitutes 7% of global CO2 emission as one tonne of cement produced generates one tonne of CO2 to the atmosphere. Besides, the waste generation is anothercommon issue which can cause air and soil pollution if the waste without proper management. Hence, utilization of wastes such as microwave incinerated rice husk ash (MIRHA), silica fume (SF) and fly ash-(FA) is one of the- feasible ways which contribute towards sustainable development and construction. An investigation into the potential use of cement replacement materials has been carried out. Up to 20% of cement of DSCC is replaced by MIRHA, SF and FA in a specific ratio. Suitable mix design was developed with different water to binder ratio, dosage of superplasticizer, different combinations of binders, and volume fraction of steel fibers to minimize the water and superplasticizer without sacrifices the self compacting abilities.